Christian circulations : global Christianity and the local church in Penang and Singapore, 1819-2000 - DeBernardi, Jean Elizabeth (NUS Press, 2020)
"In postcolonial Singapore and Malaysia, Pentecostal megachurches dominate the Christian landscape, but the "big four" Protestant churches--Anglican, Methodist, Presbyterian and Brethren--remain religions of heritage for many. Sixty Malaysian and nineteen Singaporean assemblies identify themselves as Christian Brethren, and most trace their roots to independent local churches formed in Penang and Singapore in the 1860s. After World War II, the Brethren promoted new forms of evangelical practice, and former Brethren elders founded independent churches, from charismatic local churches to Pentecostal megachurches. This study is a transregional history of the Brethren movement and its emplacement in Singapore and Malaysia, but is also a history of discontinuous continuities that have shaped the modern field of religious practice in China and Southeast Asia."--Publisher description.